Tactics of patient management of alopecia after Covid-19 - Nazim Kutty, Nafeen Kutty (Запорізький державний медичний університет, 2021)
Introduction. COVID-19 is a new viral infection, the prevalence of which is pandemic. Not only new cases of the disease are registered in the world every day, but also various types of complications or consequences of coronavirus disease transmission are recorded. Dermatology is no exception, as it is widely reported that skin vasculopathies occur when infected with this virus. According the third wave of active disease, doctors are recording such long-term effects of COVID-19 as diffuse hair loss.
Keywords: тези